Understanding about the classification of pulp inflammation - Trijoedani Widodo (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2007)
Since most authors use the reversible pulpitis and irreversible pulpitis classification, however, many dentists still do not implement these new classifications. Research was made using a descriptive method by proposing questionnaire to dentists from various dental clinics. The numbers of the dentists participating in this research are 22 dentists. All respondents use the diagnosis sheet during their examinations on patients. Nonetheless, it can't be known what diagnosis card used and most of the dentists are still using the old classification. Concerning responses given towards the new classification: a) the new classification had been heard, however, it was not clear (36.3%); b) the new classification has never been heard at all (63.6%). Then, responses concerning whether a new development is important to be followed-up or not: a) there are those who think that information concerning new development is very important (27.2%); b) those who feel that it is important to have new information (68.3%); c) those who think that new information is not important (8%). It concluded that information concerning the development of classification of pulp inflammation did not reach the dentists.